Hawkes Learning Company: The Transition from Traditional to Agile Governance - Simmons, Gerald R.; Patrick, Angela; Calk, Russell (Rusty) (Journal of Leadership, Accountability and Ethics, 2019)
Effective and responsive governance can be the key to a company's ability to deliver value and competitiveness. This case study explores Hawkes Learning Company making the switch from traditional software governance to semi-agile governance. The research questions addressed in this case identify the challenges and complexities that can exist in an organization that has adopted agile. The company saw favorable results after operationalizing agile in several of its project teams. Leadership methods included a combination of servant style leadership and others, depending on the personnel and operational environment.